Aphids (Homoptera: Aphidoidea) from the Misiones province, Argentina - Nickel, Osmar (2014)
Aphids of 44 species belonging to 30 genera and 4 families trapped in water filled Moericke type yellow trays are listed. The seazonal flight activity of the most frequently trapped species is presented. From the total trapped only four species Microparsus (Picturaphis) vignaphilus (Blanchard), M. (Picturaphis) brasiliensis (Moreira), Lizerius tuberculatus (Blanchard) and Geopempligus floccosus (Moreira) are neotropical. Therefore the regional aphid fauna is characterized by the predominance of cosmopolitan species. Trapping took place at four localities from July 1978 through January 1981.